Preparedness for Zoonotic Pandemics of Respiratory Potential: A Narrative Review of Cross-Training and Resource Allocation Models - Albalawi, Khalid Mohammed; Hawaz, Hassan Eisi Mohammed; Sahli, Khalid Mohammed Abdullah; Homdi, Abdulaziz Abdullah Ali; Halawi, Abdulrahman Mohammed Aqeel; Hamdi, Yahya Jaber Ahmed; Najmi, Hussain Ahmed Mohammed; Mobarki, Khalid Ahmed Yahya; Abdullah, Mohammed Saad; Muqri, Talal Mohmmed; et al. (Saudi Journal of Medicine and Public Health, 2024)
Background: The 21st century has witnessed multiple zoonotic respiratory outbreaks with pandemic potential, including SARS-CoV-1, H1N1 influenza, MERS-CoV, and SARS-CoV-2. These events consistently stress-test health systems, revealing critical vulnerabilities in surge capacity, inter-professional coordination, and resource logistics beyond the intensive care unit. The siloed nature of traditional healthcare preparedness often falters under the complex, cross-cutting demands of a pandemic. Aim: This narrative review aims to synthesize evidence from recent zoonotic respiratory outbreaks to critically evaluate preparedness models, with a specific focus on interdisciplinary cross-training and dynamic resource allocation strategies across public health, radiography, pharmacy, and allied health/security personnel. Methods: A comprehensive literature search was conducted across PubMed, Scopus, and Web of Science databases (2010-2024). Results: Analysis indicates that fragmented preparedness causes reactive strain, highlighting the need for proactive, scalable frameworks that combine pathogen-specific knowledge with system strengthening. Key findings stress the importance of cross-training protocols, the use of teleradiology and mobile imaging, pharmacy supply chain redundancy with ethical allocation frameworks, and the role of trained health assistants in screening and flow management. Incorporating these interdisciplinary elements in scenario planning is essential. Conclusion: Resilience against future respiratory zoonoses requires a deliberate shift from siloed, hospital-centric preparedness to integrated, system-wide strategies. Investing in interoperable cross-training protocols, agile resource-sharing agreements, and digital health infrastructures across professions can build the adaptive capacity necessary to manage surge demands while maintaining essential health services.